2023
DOI: 10.1667/rade-22-00148.1
|View full text |Cite
|
Sign up to set email alerts
|

Considerations of Medical Preparedness to Assess and Treat Various Populations During a Radiation Public Health Emergency

Abstract: During a radiological or nuclear public health emergency, given the heterogeneity of civilian populations, it is incumbent on medical response planners to understand and prepare for a potentially high degree of inter-individual variability in the biological effects of radiation exposure. A part of advanced planning should include a comprehensive approach, in which the range of possible human responses in relation to the type of radiation expected from an incident has been thoughtfully considered. Although ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 193 publications
0
4
0
Order By: Relevance
“…Biological sex-differences in normal tissue response to radiation injury have been reported by multiple labs (Jones et al, 2019;Fish et al, 2021;Sridharan et al, 2021;Brickey et al, 2022;Cosar et al, 2022;Orschell et al, 2022;Patterson et al, 2022;Andruska et al, 2023;Broustas et al, 2023;Gibbs et al, 2023;Singh et al, 2023) and the efficacy of candidate medical Frontiers in Physiology frontiersin.org countermeasures (MCMs) for radiation toxicity have also been shown to vary based on biological sex (DeBo et al, 2015;Daniel et al, 2020;DiCarlo et al, 2021;Winters et al, 2023). Consistent with our prior studies, we have validated increased sensitivity to radiation-induced pneumonitis in male rats compared to agematched female rats as evidenced by increased breathing rate, higher infiltration of immune cells in the lung, and reduced survival (Fish et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Biological sex-differences in normal tissue response to radiation injury have been reported by multiple labs (Jones et al, 2019;Fish et al, 2021;Sridharan et al, 2021;Brickey et al, 2022;Cosar et al, 2022;Orschell et al, 2022;Patterson et al, 2022;Andruska et al, 2023;Broustas et al, 2023;Gibbs et al, 2023;Singh et al, 2023) and the efficacy of candidate medical Frontiers in Physiology frontiersin.org countermeasures (MCMs) for radiation toxicity have also been shown to vary based on biological sex (DeBo et al, 2015;Daniel et al, 2020;DiCarlo et al, 2021;Winters et al, 2023). Consistent with our prior studies, we have validated increased sensitivity to radiation-induced pneumonitis in male rats compared to agematched female rats as evidenced by increased breathing rate, higher infiltration of immune cells in the lung, and reduced survival (Fish et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These risks depend on factors such as the type, dose, and dose rate of radiation, as well as an individual’s variability in biological responses to radiation exposure, which includes differences in sex, age, immune response, and metabolism. Consequently, there is an urgent demand for new MCMs capable of effectively mitigating and treating multiple organ injuries induced by radiation in diverse populations following a radiological or nuclear mass casualty incident ( 10 ). Recently, Gupta et al ( 3 , 4 ) reported that treatment with AA-ORS could decrease radiation-induced GI injury, increase electrolyte absorption, prevent antigen translocation, and reduce inflammation, subsequently improving intestinal mucosal barrier function in male NIH Swiss mice exposed to TBI.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of reports have demonstrated that the same type and dose of radiation exposure could result in different levels of injury in male and female mice (6)(7)(8)(9); therefore, the same MCM candidates may have different efficacy in different sexes of animal models (10), indicating the complex mechanisms of radiation injury. There is a pressing need for new MCMs that demonstrate high efficacy and do not pose any toxicity to effectively mitigate and treat acute radiation syndrome (ARS) in different sexes of radiation victims.…”
Section: Introductionmentioning
confidence: 99%
“…Given the imminent public health emergency regarding the exposure of individuals to ionizing radiation in hospital environments, it is essential that advanced planning is carried out to bring together collaborative efforts, as well as strategic investments in research that aim to understand better, diagnose, mitigate and treat the impact of radiation on the human body (DICARLO, 2021;WINTERS et al 2023). In this sense, it is essential to understand the concept of Public Health in order to preserve users in the hospital context.…”
Section: Introductionmentioning
confidence: 99%